ASPEK HUKUM DALAM PENATAAN MINI MARKET DI KOTA SAMARINDA - Renanta Leona Yunanta (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTIndonesia is the largest country in Asia whose average population lives as traders, especially traditional traders in the market, but now people are starting to have advanced thinking with the modern market, but each has its advantages and disadvantages each time I will discuss how Mushrooming of modern market or mini market in Indonesia especially in Kalimantan. Minimarket is no longer a foreign term for the general public, especially those living in big cities, Minimarket is an intermediary marketer between producers and end consumers where the activity is to carry out retail sales, Local government is the most authorized party to regulate and issue all policies and control the running of a policy in a region, The next local government in this case in making policies about minimarket management should be guided and referring to both legislation, Minimarket is a market that is managed with modern management, generally there are urban areas, As a provider of goods and services with good quality and service to consumers In the wakut 2 years of Indomaret and Alfamidi and many other minimarkets scattered in various districts of Samarinda city. Until now there has been no local regulations or regulation of the mayor of Samarinda who formally regulates minimarket arrangement. However, there are only rules that apply in minimarket establishment in Samarinda City which then must be adhered by the investors Indomaret and Alfamart.